Methoden und Aufgaben der Geschichte der Geographie - Beck, Hanno (ERDKUNDE, 1954)
From 1840 onwards a number of German geographers has paid more than passing attention to the history of their subject. At that time the essential ideas for an exact history of geography formulated by ]. G. Lüdde and J. Löwenberg were overlooked because of the dominant interest in exploration. Since then various works on the history of geography have been devoted exclusively to the history of exploration, ignoring the fact that exploration is by no means the only or even a necessary concern of a geographer. History of geography has to do no more and no less than to show the share that geography had in the discoveries, and also how this subject developed into a distinctive field of knowledge. At present several German geographers are attempting to prepare monographs on the history of geography stricto sensu. It is suggested that in the first instance the history of present day controversies should be dealt with.